Host specificity and phytochemical constituents of mistletoe and twigs of parasitized plants: Implications for blanket application of mistletoe as cure-all medicine - Isikhuemen, E.M.; Olisaemeka, U. O.; Oyibotie, G. O. (Journal of Medicinal Herbs and Ethnomedicine, 2020)
A study on host specificity and phytochemical constituents of leaves of mistletoe and parasitized twigs of seven host trees/shrubs was conducted in University of Benin, Benin City, Nigeria. Plant height and location were measured with Nikon Laser Rangefinder (Forestry 550) and GPS respectively while occurrence and count of mistletoe on host plants was largely anecdotal/visual. Phytochemical analyses were conducted at Faculty of Agriculture Science/Soil Laboratory, University of Benin, Benin City, Nigeria while data were subjected to One-way Analysis of Variance and means separated using Duncan Multiple Range Test (p=0.05). Results revealed mistletoe were largely generalists, and contained more phytochemicals than host plants. Tapinanthus ogowensis from Moringa oleifera was richest in alkaloid; Phragmanthera nigritana on Citrus sinensis, Tapinanthus ogowensis on Moringa oleifera and Phragmanthera capitata on Calliandra portoricensis recorded highest phenol content and differences among them were not significant (p<0.05). Phragmanthera capitata on Spondias mombin had significantly higher tannins than other mistletoe and host plants (p<0.05). P. capitata on S. mombin recorded best for saponin and flavonoid while P. capitata on Psidium guajava, Loranthus micranthus on Persia americana and P. capitata on C. portoricensis recorded more anthraquinone and were not significantly different from each other p<0.05. While the marked variation in phytochemicals in leaves of mistletoe and twigs of host plants is noteworthy; the study sufficiently established that ecological idiosyncrasies, time/season and varied environmental phenomena strongly influence incidence and/or buildup of secondary metabolites. The foregoing should serve as benchmark in selection and/or use of mistletoe for resolving infirmities.